Diffusion of frugal innovation and innovativeness in low-income contexts - Margraf, Philipp (2019)
This research examines the Diffusion of Innovation (DOI) in Base of the Pyramid (BOP) markets in the context of Frugal Innovation as well as the characteristics of innovative consumers in low-income markets. It is divided into one qualitative, exploratory and one quantitative study. Study 1 analysed the Diffusion of Frugal Innovation and consumption behaviour in Base of the Pyramid (BOP) markets, using Rogers’ (1983) Diffusion of Innovation (DOI) theory to guide interviews with 10 marketers that introduced frugal innovations into the BOP market. Study 2 analysed innovative consumers at the BOP in the favelas of Heliopolis and Jardim Angela in Sao Paulo, Brazil. The research was conducted with a questionnaire that was handed out in person. It included the Motivated Consumer Innovativeness scale to identify innovative consumers and tested its correlates with Opinion Leadership, Price Sensitivity, Susceptibility to Normative Influence and Consumer Independent Judgement as well as the socioeconomic characteristics of low-income consumers. The research found that the diffusion of frugal innovations at the BOP differs from conventional innovations due to the characteristics of low-income markets and frugal innovations. Word of mouth plays a far more important role in a market where modern means of advertising are hardly used, and Affordability has to be ensured by low prices and additional financing options to reach large parts of the population. At the same time successful innovations need to meet high quality standards. Furthermore, it was established that there exist innovative consumers in BOP markets that are looking for functional products that solve a need for them and products that bring them joy and pleasure. These innovative consumers are more price sensitive than their up-market equivalents and they tend to be strongly influenced by the beliefs and opinions of their peers in their purchasing behaviour. Also, innovative consumers tend to be younger and more active on social media, although this medium does only play a minor role in the marketing and communication efforts of companies. However, a slow transition to a more digital consumer at the BOP is taking place with digital financial services and telemedicine apps being among the most successful frugal innovations. This provides an opportunity for companies to further increase their communication with remote consumers in lowincome contexts and enhance their understanding of this part of the population.